Industrial training final report : Sam Meerkat (M) Sdn. Bhd. / Aliana Abu Talib - Abu Talib, Aliana (Universiti Teknologi MARA, Pulau Pinang, 2024)
SAM Meerkat is a distinguished provider of system integration services, catering to multinational companies in industries such as Hard Disk Drive, Solar, Semiconductor, and LED. Renowned for its vertically integrated approach, the company offers a comprehensive range of services supported by in-house capabilities, including machining, sheet metal fabrication, surface treatment processes, and assembly operations. This integrated model allows SAM Meerkat to deliver high-quality, customized engineering solutions that meet the diverse needs of its global clientele. At the core of SAM Meerkat’s operations is its expertise in equipment manufacturing and integration. The company excels in producing equipment designed to meet both high-mix, low- volume and high-mix, high-volume requirements. With a team of highly skilled Electro Mechanical and Electrical Engineers, SAM Meerkat can integrate up to 12,000 parts per machine, ensuring precision and reliability. Additionally, the company is equipped with a Class 10K Cleanroom facility, enabling it to handle high-precision and contamination-sensitive assembly projects.